Analisis Gaya Kepemimpinan, Lingkungan Kerja dan Kedisiplinan Kerja Terhadap Semangat Kerja Karyawan pada PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Sigli - Amransyah, Amransyah; Kamaruddin, Kamaruddin (Aceh Cooperative Care, 2025)
The objective of this study was to demonstrate the influence and contribution of leadership style, work environment, and discipline in improving employee morale. The study was conducted on 62 employees of UP3 PT PLN (Persero) Sigli in Pidie Regency. Quantitative research was conducted using path analysis. The results showed that (1) partially, leadership style, work environment, and discipline had a significant direct and indirect influence on employee morale, amounting to 59.01%, 65.49%, and 46.11%, respectively. (2) Simultaneously, all three contributed positively to improving morale, amounting to 62.5%. (3) There was a moderate causal relationship between the variables of work environment, work discipline, and discipline.